Genomic and functional analysis of the mucinolytic species Clostridium celatum, Clostridium tertium, and Paraclostridium bifermentans - Candeliere, Francesco; Musmeci, Eliana; Sola, Laura; Amaretti, Alberto; Raimondi, Stefano; Rossi, Maddalena (Frontiers in Microbiology, 2024)
Mucins are large glycoproteins whose degradation requires the expression of several glycosil hydrolases to catalyze the cleavage of the oligosaccharide chains and release monosaccharides that can be assimilated. In this study, we present a characterization on the strains Clostridium celatum WC0700, Clostridium tertium WC0709, and Paraclostridium bifermentans WC0705. These three strains were previously isolated from enrichment cultures on mucin of fecal samples from healthy subjects and can use mucin as sole carbon and nitrogen source. Genome analysis and in vitro functional analysis of these strains elucidated their physiological and biochemical features. C. celatum WC0700 harbored the highest number of glycosyl hydrolases specific for mucin degradation, while P. bifermentans WC0705 had the least. These predicted differences were confirmed growing the strains on 5 mucin-decorating monosaccharides (L-fucose, N-Acetylneuraminic acid, galactose, N-acetylgalactosamine, and N-acetylglucosamine) as only source of carbon. Fermenting mucin, they all produced formic, acetic, propionic, butyric, isovaleric, and lactic acids, and ethanol; acetic acid was the main primary metabolite. Further catabolic capabilities were investigated, as well as antibiotic susceptibility, biofilm formation, tolerance to oxygen and temperature. The potential pathogenicity of the strains was evaluated through in silico research of virulence factors. The merge between comparative and functional genomics and biochemical/physiological characterization provided a comprehensive view of these mucin degraders, reassuring on the safety of these species and leaving ample scope for deeper investigations on the relationship with the host and for assessing if some relevant health-promoting effect could be ascribed to these SCFA producing species.